2022
DOI: 10.1097/gco.0000000000000811
|View full text |Cite
|
Sign up to set email alerts
|

An update of diagnostic efficacy of ultrasound and magnetic resonance imaging in the diagnosis of clinically significant placenta accreta spectrum disorders

Abstract: Purpose of reviewSystematic screening and diagnosis of placenta accreta spectrum disorder (PAS) either by ultrasound or magnetic resonance imaging (MRI) would allow referral of high-risk women to specialized multidisciplinary teams. We aimed to report recent findings regarding the diagnostic accuracy of ultrasound and magnetic resonance imaging in the diagnosis of PAS. Recent findingsRecent evidence from the literature shows that both ultrasound and MRI are good tests to identify PAS in high-risk populations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…This technology does not require the use of radiation, and is more safer for pregnant women and fetuses. Moreover, MRI imaging will not be affected by fetal movement or fetal position, and can be checked in different pregnancy periods, which is very helpful for the early diagnosis and follow-up of placenta previa [7]. In addition, MRI can also comprehensively evaluate multiple parameters, such as the thickness of placenta, the length of cervix, the distance between placenta and cervix, the size and shape of the internal orifice of cervix, etc., to judge the type and severity of placenta previa from multiple perspectives, and more accurately diagnose and evaluate [8].…”
Section: Accuracy Of Mri In Diagnosis Of Placenta Previamentioning
confidence: 99%
“…This technology does not require the use of radiation, and is more safer for pregnant women and fetuses. Moreover, MRI imaging will not be affected by fetal movement or fetal position, and can be checked in different pregnancy periods, which is very helpful for the early diagnosis and follow-up of placenta previa [7]. In addition, MRI can also comprehensively evaluate multiple parameters, such as the thickness of placenta, the length of cervix, the distance between placenta and cervix, the size and shape of the internal orifice of cervix, etc., to judge the type and severity of placenta previa from multiple perspectives, and more accurately diagnose and evaluate [8].…”
Section: Accuracy Of Mri In Diagnosis Of Placenta Previamentioning
confidence: 99%
“…An updated review by Fratelli et al 2022, 12 on the diagnostic accuracy of US and MRI in PAS disorders, showed that the advantages of each imaging modality counteract the limitations of the other. Thus, the disadvantages of US, such as operator-dependence and limited penetration and narrow field of view, are compensated by MRI's reproducible large field of view.…”
Section: Introductionmentioning
confidence: 99%
“…MRI has a wide field of view and high contrast resolution to describe the characterization of placental anatomy [9]. MRI is an effective imaging modalities for guiding management of PP [10]. Due to the thinning uterine segment, PP is often combined with placenta accreta or increta.…”
mentioning
confidence: 99%
“…9 MRI is an effective imaging modalities for guiding management of PP. 10 Due to the thinning uterine segment, PP is often combined with placenta accreta or increta. PP is associated with high incidence of intraoperative hemorrhage (IPH) and postpartum hemorrhage, need for blood transfusion and hysterectomy, which is considered a severe complication of pregnancy, and even death.…”
mentioning
confidence: 99%